Linguistic expression of intangible cultural heritage in "Baburnama": subject, object, addressee - Daniyar, A.A.; Ilker, A.; Akhmetova, M.K. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
The intangible cultural heritage of the Great Silk Way Road has the core role in historical area. It covers various spheres of life and is reflected in traditions, customs, languages, music, dances, crafts, ceremonies, legends and historical events. In the written heritage of "Baburnama", the author provides the centuries-old Turkic identity and cross-country features that arose from Central Asia, associated with the lands of Afghanistan, India, namely geographical, biological, medical, literary, historical, political, cultural and other relations. Babur's personal experiences and observations, his philosophical reflections and assessments of various cultural and socio-political phenomena are transmitted through "Baburnama". Thus, this work serves not only as a historical documents events, but also serves as an important source for understanding the cultural context of the era. The article depicts linguistic expression of intangible cultural heritage in "Baburnama". The primary focus was on the semantic syntactic components of the propositions in Babur's sentences such as, subject, object, and addressee. The actant was noted in the scripts of that era's intangible cultural heritage, based on the sentence's syntax structure. The text's substance and its feature of utilizing the many forms of intangible cultural heritage from the Babur era in contemporary Kazakh society are decided upon based on the study examples that were gathered.